2011
DOI: 10.1016/j.pain.2010.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Genomic loci and candidate genes underlying inflammatory nociception

Abstract: Heritable genetic factors contribute significantly to inflammatory nociception. To determine candidate genes underlying inflammatory nociception, the current study used a mouse model of abdominal inflammatory pain. BXD recombinant inbred (RI) mouse strains were administered the intraperitoneal (IP) acetic acid test and genome-wide quantitative trait locus (QTL) mapping was performed on the mean number of abdominal contraction and extension movements in three distinct groups of BXD RI mouse strains in two separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that genetically distinct inbred mouse strains display variable somatosensory behaviors such as pain and itch (Green et al, 2006; Nair et al, 2011). We set out to identify transcripts that were co-regulated with itch behaviors across such mouse strains.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that genetically distinct inbred mouse strains display variable somatosensory behaviors such as pain and itch (Green et al, 2006; Nair et al, 2011). We set out to identify transcripts that were co-regulated with itch behaviors across such mouse strains.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a clear influence of sex is demonstrated, however, not being directly linked to a genetic effect mapping to the sex chromosomes. The present study lays the basis for further studies to dissect the genetic contribution to pain after SCI injury, as has been performed in peripheral nerve injury models (Costigan et al., ; Fortin et al., ; Nissenbaum et al., ; Nair et al., ). One strategy for identifying candidate genes and pathway regulated by the identified regions is to use expression QTL mapping using microarrays as has been successfully performed in other traits (Pravenec et al., ).…”
Section: Resultsmentioning
confidence: 71%
“…This QTL is between 26.10 and 48.24 Mb and is not overlapping with any of our newly detected QTLs. From the table, there is only one QTL in mice on chromosome 3 (54.93–60.47 Mb) (Nair et al., ) that is in synteny with our QTL on rat chromosome 2 (144.34–149.86 Mb). However, the lack of overlap is not surprising in view of our previous finding of genetically different regulation of pain induced by injury to the peripheral and CNSs (Dominguez et al., ,b).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Statistical significance was defined at P <0.05. Heritability was determined as h 2 = VA/(VA + VE), where VA is the additive genetic variation estimated by the between-strain variance and VE is the environmental variance estimated by the within-strain variance from the ANOVA results [34]. …”
Section: Methodsmentioning
confidence: 99%